The effect of relaxation gymnastics education on the anxiety of pregnant women in the new normal era - Wulandari, Baiq Rina; Kusmiyati, Yuni; Gunarmi, Gunarmi (Alma Ata University Press, 2024)
Background: Currently the government is implementing a new normal policy regarding the Covid-19 pandemic. Pregnancy in the new normal era still causes anxiety among pregnant women because the Covid-19 pandemic as a whole has not yet ended due to information regarding the condition of pregnant women who are very likely to still be infected with the Covid-19 virus. Remembering that you have to be in the hospital and have direct contact with medical staff.Objectives: The research aims to determine the effect of relaxation exercise education using video and leaflet media on the anxiety of pregnant women in the new normal era.Methods: This research is an experiment with a pre-test-post-test control group design. There were 62 pregnant women respondents who were selected using simple random sampling technique. The instrument uses the Google-shaped Coronavirus Anxiety Scale (CAS) questionnaire. The analysis used the Independent T-test to determine differences in anxiety between treatment groups with video media and leaflet media.Results: The results of the study showed that there was an insignificant difference in reducing anxiety for pregnant women with relaxation training education using video media and leaflets. There was no significant difference in pre-posttest1, pre-posttest2 and pre-posttest3 anxiety scores (p>0.05). There is an influence of relaxation sports education using video media and leaflets on reducing the anxiety of pregnant women in the new normal era.Conclusions: Pregnancy exercise education using video media and leaflets can reduce the anxiety of pregnant women, so it is hoped that pregnant women will know and understand how important it is to deal with anxiety during pregnancy. The more often a mother does pregnancy exercises, the more calm she will be during pregnancy.